2020
DOI: 10.1111/ijcp.13876
|View full text |Cite
|
Sign up to set email alerts
|

The lack of association between dietary antioxidant quality score with handgrip strength and handgrip endurance amongst Tehranian adults: A cross‐sectional study from a Middle East country

Abstract: Objective The association between dietary antioxidant quality score (DAQS) and handgrip strength (HS) and handgrip endurance (HE) is still unclear. We aimed to investigate whether adherence to dietary antioxidant quality score (DAQS) is associated with handgrip strength (HS) and handgrip endurance (HE) amongst adults in Tehran. Methods This cross‐sectional study was conducted on 270 (43.7% males, mean age 37 years and 56.3% females, mean age 35 years) apparently healthy adult subjects (53.2% were married) sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Vitamin E is known to promote the repair of membrane injury in skeletal muscle cells (45). A study showed that increased vitamin E intake enhanced muscle mass (46) while other studies indicated that vitamin C supplementation reduced oxidative stress, and that increased dietary intake of the vitamin C alleviated muscle loss in younger women (47, 48). Besides, in skeletal muscle physiology, vitamin C helps with carnitine and collagen production and has a positive association with muscle (49).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is known to promote the repair of membrane injury in skeletal muscle cells (45). A study showed that increased vitamin E intake enhanced muscle mass (46) while other studies indicated that vitamin C supplementation reduced oxidative stress, and that increased dietary intake of the vitamin C alleviated muscle loss in younger women (47, 48). Besides, in skeletal muscle physiology, vitamin C helps with carnitine and collagen production and has a positive association with muscle (49).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, when the intake of five components decreased below 2/3 of the RDI, a value of 0 was applied as well as a score of 1 was given when the intake exceeded 2/3 of the RDI. As a result, the overall DAQS ranged between 0 which indicated lowest antioxidant quality and 5 that shows highest antioxidant quality [37,38].…”
Section: Dietary Assessments and Calculation Of Daqsmentioning
confidence: 99%